Financial Sector Assessment : Croatia - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) summarizes the Financial Sector Assessment Program (FSAP) report for Croatia. The FSAP mission visited Zagreb during the period September 3-14,200l and discussed its preliminary findings with the representatives of the Croatia National Bank (CNB) and Ministry of Finance (MoF) on September 14, 2001. The mission also discussed the assessments of observance of codes and standards with relevant government offices and agencies. An assessment was also made of the legal and institutional arrangements for Anti-Money Laundering/Combating the Financing of Terrorism (AMLKFT). The final FSAP report was submitted in November 2002.